pH-Sensitive and Long-Circulation Nanoparticles for Near-Infrared Fluorescence Imaging-Monitored and Chemo-Photothermal Synergistic Treatment Against Gastric Cancer - Zhou, Yun; Sun, Xuanzi; Zhou, Liansuo; Zhang, Xiaozhi (Frontiers in Pharmacology, 2020)
Gastrectomy is the primary therapeutic option for gastric cancer. Postoperative treatment also plays a crucial role. The strategy to improve the postoperative prognosis of gastric cancer requires a combined system that includes a more efficient synergistic treatment and real-time monitoring after surgery. In this study, photothermal-chemotherapy combined nanoparticles (PCC NPs) were prepared via π-π stacking to perform chemo-photothermal synergistic therapy and continuous imaging of gastric cancer. PCC NPs had a spherical morphology and good monodispersity under aqueous conditions. The hydrodynamic diameter of PCC NPs was 59.4 ± 3.6 nm. PCC NPs possessed strong encapsulation ability, and the maximum drug loading rate was approximately 37%. The NPs exhibited extraordinary stability and pH-response release profiles. The NPs were rapidly heated under irradiation. The maximum temperature was close to 58°C. PCC NPs showed good biocompatibility both in vitro and in vivo. Moreover, the NPs could effectively be used for in vivo continuous monitoring of gastric cancer. After one injection, the fluorescent signal remained in tumor tissues for nearly a week. The inhibitory effect of PCC NPs was evaluated in a gastric cancer cell line and xenograft mouse model. Both in vitro and in vivo evaluations demonstrated that PCC NPs could be used for chemo-photothermal synergistic therapy. The suppression effect of PCC NPs was significantly better than that of single chemotherapy or photothermal treatment. This study lays the foundation for the development of novel postoperative treatments for gastric cancer.